APLIKASI MONITORING PERBAIKAN DAN PELAYANAN MAINTENANCE SERVIC CENTER (MSC) INDIHOME PADA PT. TELKOM MAKASSAR BERBASIS WEB - Nurdiansah; Heriadi; Michael Oktavianus (Journal of Innovation Research and Knowledge, 2021)
PT Telekomunikasi Indonesia Tbk (Persero) commonly referred to as Telkom Indonesia or Telkom is an information and communication company as well as a complete telecommunications service and network provider in Indonesia. Telkom claims to be the largest telecommunications company in Indonesia, with a total of 15 million fixed-line telephone subscribers, 104 million. The purpose of this study was to design an Application for Monitoring Repair and Maintenance Service Center (MSC) Indihome At PT. Web-Based Telkom that can provide convenience in the process of monitoring improvements and services. Designing an application that is able to streamline the service and repair process. Test results obtained By using a website system designed for reporting customer complaints that occur, the report will be inputted into the website and will be handled by the technician concerned. With the notification in the system, the system simplifies the process of monitoring incoming customer complaints.